2018
DOI: 10.1108/ijge-04-2018-0032
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian women’s entrepreneurial profile and intention

Abstract: Purpose The paper aims to investigate the existence of typical preferred behaviours that might characterize Brazilian women’s entrepreneurial profile and whether this profile influences their motivation to undertake a venture. Design/methodology/approach Following the evolution of the literature on women entrepreneurship, the study criticizes the rational view that conceives entrepreneurship as a universal phenomenon and immune to gender. A quantitative approach based on multivariate data analysis (structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
18

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(68 citation statements)
references
References 62 publications
0
50
0
18
Order By: Relevance
“…In addition, prior studies have found that self-efficacy is a reliable predictor in educational settings (Atiya et al, 2019;Krakauer et al, 2018), since students participating in entrepreneurship courses present high entrepreneurial intent (Küttim, Kallaste, Venesaar, & Kiis, 2014). Also, by learning about entrepreneurship, students tend to develop their own strategies to maintain motivation and deal with future chances of success (Newman et al, 2019).…”
Section: Entrepreneurial Self-efficacymentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, prior studies have found that self-efficacy is a reliable predictor in educational settings (Atiya et al, 2019;Krakauer et al, 2018), since students participating in entrepreneurship courses present high entrepreneurial intent (Küttim, Kallaste, Venesaar, & Kiis, 2014). Also, by learning about entrepreneurship, students tend to develop their own strategies to maintain motivation and deal with future chances of success (Newman et al, 2019).…”
Section: Entrepreneurial Self-efficacymentioning
confidence: 99%
“…Moreover, when referring to behavioral aspects, literature hasn't reached a consensus of what variables should be considered (Bignotti & Le Roux, 2016;Krakauer et al, 2018), since some authors endorse the use of self-efficacy (Asimakopoulos et al, 2019;Miao et al, 2017;Newman et al, 2019;Zhao et al, 2005), while others entrepreneurial characteristics (Koe et al, 2012;Moraes et al, 2018;Rocha & Freitas, 2014;Vodă & Florea, 2019), when studying the personal-level characteristics that affect EI.…”
Section: Entrepreneurial Intention Influencersmentioning
confidence: 99%
See 2 more Smart Citations
“…(Markman, Baron, 2003) Resolutividade/ Eficácia "As características comportamentais que se destacam na maneira como os empreendedores atuam também podem influenciar a vontade de se tornar um empreendedor." (Krakauer, 2018) Visão estratégica "Analisar os subsistemas do negócio, desenhar projetos e realizar intervenções a fim do desenvolvimento do negócio" (Ploum, 2018).…”
Section: Competências Literatura Descriçãounclassified